2011
DOI: 10.1007/s00392-010-0276-x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety trait in patients with stress-induced cardiomyopathy: a case–control study

Abstract: Background Stress-induced Tako-tsubo cardiomyopathy (TTC) is an acute cardiac syndrome, mimics ST elevation myocardial infarction (STEMI), largely confined to postmenopausal women, frequently precipitated by a stressful event. The pathogenesis of TTC is still unknown. Some authors hypothesized a possible connection between TTC and anxiety disease, but no previous study analyzed the relationship between anxiety trait and TTC. This study sought to assess the potential role of anxiety trait in the development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 30 publications
0
21
2
Order By: Relevance
“…Psychological approaches to reveal the aetiology of TTC are sparse and reveal conflicting results 4 21. In the present study, TTC patients were screened in detail for predisposing attributes, but our findings neither lend support for psychiatric or personality characteristics nor for an increased occurrence of general social or work hassles.…”
Section: Discussioncontrasting
confidence: 63%
“…Psychological approaches to reveal the aetiology of TTC are sparse and reveal conflicting results 4 21. In the present study, TTC patients were screened in detail for predisposing attributes, but our findings neither lend support for psychiatric or personality characteristics nor for an increased occurrence of general social or work hassles.…”
Section: Discussioncontrasting
confidence: 63%
“…Manfredini et al found that patients most frequently present on Mondays and argued that start of the week is associated with greater prevalence of stress 13. In contrast, a study by Del Pace et al found no difference in rates of anxiety between takotsubo cardiomyopathy and STEMI patients, rejecting anxiety as a potential trigger for takotsubo cardiomyopathy 14. Interestingly, Yaqub et al recently reported two distinct clinical phenotypes of takotsubo cardiomyopathy concluding that emotional stress-induced takotsubo cardiomyopathy required less intense haemodynamic support when compared with idiopathic/physical stress-induced takotsubo cardiomyopathy 15.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The prevalence of depression and anxiety disorders in TCC ranges from 21–60 % [1, 1619]. An increase in levels of psychological distress from admission to one-year follow-up is common [20].…”
Section: Introductionmentioning
confidence: 99%